Homeostatic model and job-organization related factors as predictors of subjective wellbeing of Mizan-Tepi university teachers - Michael Emru adesse (Bahir Dar Journal of Education)
The aim of this study was to examine factors that affect the subjective wellbeing (SWB) of university teachers, at Mizan – Tepi University (MTU), Ethiopia. Accordingly, the study employed the homeostasis theory of SWB as a theoretical framework and tested two major hypotheses. First, it was hypothesized that the homeostatic model of SWB (extraversion, emotional stability, experiential input, perceived control, self-esteem and optimism) would significantly predict the SWB of teachers. The second hypothesis was that Job- and organization-related factors (job satisfaction and organizational culture), as additional aspects of experiential input, would contribute significant unique variance in SWB above homeostatic model predictors. A sample of 162 teachers participated in this study by responding to questionnaires that included measures of the abovementioned variables. Hierarchical linear regression was used to test the hypotheses. According to the results, the homeostatic model of SWB was a significant predictor of teachers’ SWB. In this case, perceived control and optimism made unique contributions while extraversion, emotional stability and self-esteem did not make unique contributions but shared variance with one another. Besides, Job- and organization-related factors were found to be significant predictors of teachers’ SWB. Both job satisfaction and organizational culture contributed significant unique variance above the homeostatic model predictors. Based on the results of the study, it can be concluded that job- and organization- related factors join forces with homeostatic model factors in contributing to or affecting the SWB of teachers